The spaceflight vault : a history of NASA's manned missions - Mayfield, Mark. (Atlanta, GA : Whitman Pub., 2010)
For thousands of years, man has looked to the stars in wonder, but it is only recently that we have been able to travel among them, and The Spaceflight Vault: A History of NASA s Manned Missions traces the extraordinary journey from the early rocketry pioneers to the astronauts of today. Filled with hundreds of photos from the archives at Johnson Space Center, Clark University and private collections, The Spaceflight Vault is a stunning visual history of man s achievements in space. Designed as a treasured scrapbook, the vault also contains replicas of historic memorabilia such as pages from Dr. Robert Goddard s andwritten diary, written tests from the Mercury astronaut selection program, Gemini flight menus, Apollo 7 checklists, media passes from early shuttle launches, front pages from numerous issues of The Johnson Space Center Roundup and much more. No one who has ever dreamed of soaring among the stars should be without this home archive of man s journey into orbit.
Many pages contain pockets with replica documents and memorabilia.
Includes bibliographical references (p. 143).
Keywords: United States. -- National Aeronautics and Space Administration -- History; Space flights; Manned space flight